Occupational Therapy for Parenting: Perspectives of Parents With Physical Disability - Anne Honey; Jessica Peterson; Veronica O’Mara; Margaret McGrath (Occupational Therapy International)
Parenting with a physical disability often brings with it a range of challenges. Occupational therapists are well positioned to support parents to address these challenges, yet occupational therapy research and practice around parenting is relatively scarce. This paper addresses the questions: (1) How should occupational therapists support parenting occupations for people with physical disability? (2) How do parents with physical disability experience occupational therapy? An anonymous survey of 62 parents, primarily mothers, with physical disability about their experiences with parenting challenges and occupational therapy was analysed using both quantitative and qualitative techniques. Parents experienced challenges in engaging in a range of parenting tasks with children over a range of age groups. Parents reported that support was often needed and indicated that occupational therapy could assist them directly with specific parenting goals as well as the more usual biomechanical goals that influence parenting. Yet less than half of participants who received occupational therapy services reported that parenting tasks were addressed, and only one-fifth reported that their goals had been fully met. The data also indicated that the knowledge, skills, and attitudes of occupational therapists with regard to working with parents with disability can be improved. Findings suggest a need to better incorporate parenting occupations in standard occupational therapy training to increase occupational therapists’ comfort and competence in working with clients on parenting issues.